Genome Sequence of the Heteropolysaccharide-Producing Strain Lactobacillus mucosae DPC 6426 - Ryan, Paul M. (Genome Announc, 2015)
Exopolysaccharide-synthesizing Lactobacillus mucosae DPC 6426 is a heterofermentative strain, which has demonstrated cholesterol-lowering properties in an animal model of lipid-driven atherosclerosis. The genome revealed a plethora of homologues linked to carbohydrate metabolism and mucin binding.